The invisible ideological construct of advertising discourse - de Almeida, Danielle Barbosa Lins (Revista Leitura, 2019)
In light of the interpretatlve nature of discourse analysis and within the context of two advertisements of soap - Gessy, dated 1942, and Lux Luxo, dated March 2003 - the main purpose of the present article is to analyse how the discursive practices of advertising discourse allow for the reproduction and maintenance of certain ideological assumptions, such as the ones related to consumerism and gender-based issues. DOI: 10.28998/0103-6858.2007v2n40p15-26